FILSAFAT EKONOMI ISLAM: RASIONALITAS DAN RELIGIUSITAS EKONOMI - Wahyu, Bambang (Al-Infaq: Jurnal Ekonomi Islam, 2010)
This study is aimed to show the importance of epistemological study in Islamic economics fields. There are two approaches under Islamic economics: descriptive-analysis and thematic-analysis. Both have a relevancy in order to strenghten Islamic economics study. Based on epistemological approach there are two kinds of Islamic economics studies rely on its normative manner i.e. rationality of economics and religiousity of economic. And both can not be released from Islamic moral foundations.